2019
DOI: 10.1002/ese3.333
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics analysis of heat transfer in a greenhouse solar dryer “chapel‐type” coupled to an air solar heating system

Abstract: The distribution of turbulent kinetic energy (TKE), temperature, and velocity of humid air inside the greenhouse solar dryer (GHSD) was numerically investigated using 3D CFD ANSYS FLUENT code. The effect of solar radiation was coupled with the energy equations using the discrete ordinate model. Numerical simulations were based on two geometric models: Real model and model with reduced height, the solution was in good agreement with experimental data of temperature. The results of the real model showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 42 publications
(109 reference statements)
1
19
0
Order By: Relevance
“…The numerical grid of the computer domain and its specific conditions of size and quality are an essential step that defines the process of convergence of the numerical solution and the appropriate prediction of the results obtained [31,32]. In this research, the discretization of the four computational domains that included each one of the evaluated dryers, was made from the decomposition of the large computational domains in a finite number of small control volumes integrated in an unstructured grid in a three-dimensional space.…”
Section: Discretization Of the Computer Domain And Boundary Conditionsmentioning
confidence: 99%
“…The numerical grid of the computer domain and its specific conditions of size and quality are an essential step that defines the process of convergence of the numerical solution and the appropriate prediction of the results obtained [31,32]. In this research, the discretization of the four computational domains that included each one of the evaluated dryers, was made from the decomposition of the large computational domains in a finite number of small control volumes integrated in an unstructured grid in a three-dimensional space.…”
Section: Discretization Of the Computer Domain And Boundary Conditionsmentioning
confidence: 99%
“…The selection of the grid size is made once it is observed that the evaluation parameters tend to have a constant behavior independently of the numerical grid size (Figure 3). The quality of the grid was evaluated using the orthogonality criterion, for which 98.2% of the cells were in the high-quality range [62,63]. relative humidity inside the PG greenhouse were selected as the main parameters according to which the independence analysis was performed.…”
Section: Computational Domain and Meshing Processmentioning
confidence: 99%
“…The random temperature behavior is observed and it is attributed to the weather conditions. Roman-Roldan, Lopez-Ortiz, Ituna-Yudonago, Garcia-Valladares, and Pilatowsky-Figueroa (2019) performed CFD simulations of greenhouse dryer coupled with air heater. The temperature of moist air is found to be decreasing after entering the dryer space.…”
Section: Introductionmentioning
confidence: 99%